1996
DOI: 10.1002/(sici)1096-9861(19960115)364:3<439::aid-cne5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cells that express 5- hydroxytryptamine1A receptors in the nervous systems of the bowel and pancreas

Abstract: Although serotonin (5-HT)1A receptors are known to be present on neural elements in both the bowel and the pancreas, the precise location of these receptors has not previously been determined. Earlier investigations have suggested that 5-HT1A receptors are synthesized in enteric, but not pancreatic ganglia, and that they mediate pre-and postjunctional inhibition. Wholemount in situ hybridization was used to identify cells that contain mRNA encoding 5-HT1A receptors, and immunocytochemistry was employed to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 65 publications
5
46
0
Order By: Relevance
“…To date, the only data identifying a possible transmitter mediating the myenteric IPSPs comes from a limited study, which found that the 5-HT 1A receptor antagonist NAN-190 blocked IPSPs in some AH/Dogiel type II neurons [54]. Many AH/Dogiel type II neurons express 5-HT 1A receptors [64] and are hyperpolarized by 5-HT acting on these receptors [39,42]. Electrical stimulation of descending pathways including the axons of neurons containing 5-HT evokes slow EPSPs in many AH/Dogiel type II neurons [83] and blockade of 5-HT 7 receptors can convert the slow EPSPs into slow hyperpolarizations.…”
Section: Ipsps and Their Transmittersmentioning
confidence: 66%
“…To date, the only data identifying a possible transmitter mediating the myenteric IPSPs comes from a limited study, which found that the 5-HT 1A receptor antagonist NAN-190 blocked IPSPs in some AH/Dogiel type II neurons [54]. Many AH/Dogiel type II neurons express 5-HT 1A receptors [64] and are hyperpolarized by 5-HT acting on these receptors [39,42]. Electrical stimulation of descending pathways including the axons of neurons containing 5-HT evokes slow EPSPs in many AH/Dogiel type II neurons [83] and blockade of 5-HT 7 receptors can convert the slow EPSPs into slow hyperpolarizations.…”
Section: Ipsps and Their Transmittersmentioning
confidence: 66%
“…Mechanical stimulation generated by direct contact of the enterochromaffin cells with the luminal contents occurs frequently throughout the intestinal tract. Others have reported that balloon distention, puffs of nitrogen gas ejected from a pipette, and stroking with a brush evoke 5-HT release (31,32). Many of these stimuli are composed of several different forces acting simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…glucagon-like peptide 1 [GLP-1] analogues used for treating type 2 diabetes) is a successful example of this approach [4,5]. Serotonin (5-hydroxytryptamine ) receptors are expressed in rodent islets [6][7][8] and virtually all 5-HT receptors (5-HT 1-7 ) are G protein-coupled with the exception of 5-HT 3 receptors (ligand-gated K + and Na + ion channels) [9]. Recently, microarray and RNA sequencing analyses revealed transcripts of almost all 5-HT receptors in human islets [10,11].…”
Section: Introductionmentioning
confidence: 99%